Analisis Strategi Pemasaran Franchise Nyoklat Klasik Galang - Ratna Sari Dewi; Sekar Arum; Nayla Natasya; Muhammad Irsyad Hasibuan; Revandi Dewanta Tarigan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the marketing strategy of the Nyoklat Klasik Galang franchise using a descriptive qualitative approach. The results show the implementation of the marketing mix (7P) with a focus on affordable prices, strategic locations, and digital promotions. The SWOT analysis identifies the main strengths in regional exclusivity and low prices, but constrained by the dependence on raw material supply. Opportunities are growing in the current beverage trend, while the main threat is fierce competition.